Pemikiran Ekonomi Islam pada Masa Rasulullah saw: Etika dan Norma Ekonomi Islam Masa Rasulullah saw Relevansinya dalam Praktik Ekonomi Modern - Sochimin; Nurul Ngarifah (Jurnal Ilmiah Ekonomi Islam, 2025)
The growing problem of global economic inequality poses a serious challenge to modern economic practice, necessitating an approach that integrates the ethical values ​​and Islamic economic norms taught by the Prophet Muhammad (peace be upon him). The current moral crisis in the business world demonstrates that many economic practices deviate from Islamic teachings, making it crucial to re-explore the economic principles emphasized by the Prophet Muhammad (peace be upon him) for their application in a modern context. Although the Prophet Muhammad's economic principles offer solutions to contemporary problems, many economic actors still lack the understanding and application of the values ​​of monotheism, justice, and balance in their economic activities. The challenge of creating a sustainable and just economic system is increasingly pressing, necessitating an in-depth study of the relevance of Islamic economic thought in formulating current economic policies. This article is a library research study using qualitative methods. It aims to discuss several themes regarding Islamic economic thought during the time of the Prophet Muhammad (peace be upon him), economic practices and policies during his time, the economic principles taught by the Prophet Muhammad (peace be upon him), the Prophet's business ethics in history and from the perspective of the maqasid sharia (the principles of sharia), and the relevance and implementation of the Prophet's economics in the modern economic era. This article concludes that the economic thought taught by the Prophet Muhammad (peace be upon him) demonstrates that the values ​​of monotheism, justice, and balance are not only relevant but also fundamental in the modern economic context. Policies such as the prohibition of usury, the implementation of zakat, and the establishment of ethical markets provide clear direction in formulating contemporary economic policies. Although today's economic structure is more complex, the principles taught by the Prophet Muhammad (peace be upon him) are able to address challenges such as global inequality and the moral crisis in the current economy. Therefore, exploring and actualizing his economic thought is a strategic step towards designing a just, ethical, and sustainable economic system.